Diagnostic Evaluation of the Breast Using PET: Optimization of Data Acquisition and Postprocessing - Brix, G.; Henze, M.; Doll, J.; Lucht, R.; Zaers, J.; Trojan, H.; Knopp, M. V.; Haberkorn, U. (Nuklearmedizin - NuclearMedicine, 2000)
Purpose: Development and evaluation of an optimized protocol for PET examinations of the female breast with 2-F-l8-fluoro-2-deoxyglucose (F-18-FDG). Methods: All PET measurements were performed with a whole-body PET system (ECAT EXACT HR+). In order to examine the women with the breasts freely pendant, a special extension for the patient table made of carbon layer composite was designed. After data acquisition in the 3D modus, emission data were sorted into 2D sinograms using the Fourier rebinning algorithm and reconstructed by means of an ultra-fast iterative 2D algorithm (HOSP). The reconstructed emission scans were superimposed onto the corresponding transmission images. The protocol presented was evaluated in examinations on 6 women with breast lesions after the administration of 150-220 MBq F-l8-FDG. From two adjacent bed positions, emission and transmission data were acquired over periods of 20 min and 10 min, respectively. For comparison, dynamic magnetic resonance (MR) image series were acquired with a whole-body MR system (MAGNET0M SP 4000) using a double-breast coil. Results and Conclusion: Using the designed extension of the patient table, it was possible to examine corpulent women despite the limited patient port of the PET system in the prone position with the breasts freely pendant. Alongside a reduction in motion artifacts, this positioning also offers the possibility of making a direct comparison between PET and MR images. Despite the fact that the amount of F-l8-FDG applied to the patient was markedly reduced, the combination of 3D data acquisition and iterative image reconstruction resulted in excellent quality of the emission scans. By superpositioning of iteratively reconstructed emission and transmission scans, anatomical localization of breast lesions visualized on the emission scans could be improved. The postprocessing of the PET data described was completed in 60 min, this meaning that the presented concept can readily be employed in clinical practice.
Keywords: Positron emission tomography; breast cancer; 3D data acquisition; dose reduction; image fusion